THE INFLUENCE OF LEADERSHIP STYLE ON THE PERFORMANCE OF ALL EMPLOYEES WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (Case Study at PT. Deli Tebing Luhur/Jordan Bakery) - Rico Nur Ilham; Lala Merlita; Muhammad Multazam; T.M Azani; Ikram (Universitas Efarina, 2023)
In this study the population is Technical Clerical Employees of PT. Tebing Luhur Deli/Jordan Bakery, namely as many as 40 people. Because the target population is less than 100, the sampling technique used is the census method, in which the entire population is 40 Technical Clerical Employees of PT. Deli Tebing Luhur/Jordan Bakery which will be used as research samples. the first hypothesis is accepted, meaning that Leadership Style (X) has a significant effect on Job Satisfaction (Y1). the second hypothesis is accepted, meaning that Leadership Style (X) has a significant effect on Employee Performance (Y2). the third hypothesis is accepted, meaning that Job Satisfaction (Y1) is an intervening variable that mediates the effect of Leadership Style (X) on Employee Performance (Y2).